Gene targeting in melanoma therapy: exploiting of surface markers and specific promoters - Alekseenko, I.V.; Zinovyeva, M.V.; Pleshkan, V.V.; Sverdlov, E.D. (Вiopolymers and Cell, 2012)
One of the problems of gene therapy of melanoma is effective expression of therapeutic gene in tumor cells and their metastases but not in normal cells. In this review, we will consider a two-step approach to a highly specific gene therapy. At the first step, therapeutic genes are delivered specifically to tumor cells using cell surface markers of melanoma cells as targets. At the second step, a specific expression of the therapeutic genes in tumor cells is ensured. Surface markers of melanoma cells were analyzed as potential targets for therapeutic treatment. Criteria for choosing the most promising targets are proposed. The use of specific melanoma promoters allows to further increase the specificity of treatment via transcriptional control of therapeutic gene expression in melanoma cells.